Augmented Education : Bringing Real and Virtual Learning Together - Sheehy, Kieron; Ferguson, Rebecca; Clough, Gill; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Including relevant case studies and interviews with practitioners, Augmented Education explores the nature of learning where the'real world' is augmented by use of the virtual to create new learning possibilities, tools, and environments. and offers insights into the development of a pedagogy that is authentic, inclusive and enjoyable.
Keywords: Science; Science, general